OPTOELECTRONIC CONVERTERS BASED ON APV ELEMENTS - Shohbozjon Ergashev (European Science Publishing, 2023)
This work examines new applications of APV elements based on narrow-gap semiconductor materials. The physical and technical foundations of photoelectronic converters of deflection systems and optical modulators based on APV elements are analyzed. An optoelectronic device has been developed based on APV - elements with an electro-optical effect, and a sound-controlled light deflection system.
Keywords: optical modulator, abnormally high photoelectric voltage (APV), narrow-gap semiconductor material, optoelectronic conversion of optical signals.